PENGARUH BANTUAN HIBAH BEASISWA BAGI PENINGKATAN PRESTASI BELAJAR DAN PENINGKATAN KUALITAS LULUSAN SUMBER DAYA MANUSIA PENERIMA HIBAH BEASISWA PEMERINTAH PROVINSI KEPULAUAN BANGKA BELITUNG - Arka'a Ahmad Agin (JEM Jurnal Ekonomi dan Manajemen, 2019)
The regional government of the province of Bangka Belitung province has committed to increasing the budget in order to improve the quality of education, quantity, and quality of teachers, teacher welfare, and to implement 12-year compulsory education. This study aims to determine the effect of scholarship grants in the Bangka Belitung Islands Provincial Government for improving the learning achievement of scholarship grant recipients. This research is expected to provide benefits for the development of science in the application of theories related to public policy management. The population in this study were 97 people from the number of students receiving scholarship grants at tertiary institutions in the Bangka Belitung Islands Province. granting of grants is statistically significant in improving the learning achievement of recipient students. Noting the results of research that has been carried out, it is necessary for the Government of the Bangka Belitung Islands Province to continue the policy with a variety of variations that are tailored to the needs.